Exchange of information and bank deposits in international financial centres - O'Reilly, Pierce (OECD Publishing, 2019)
This paper assesses the impact of exchange of information on foreign-owned bank deposits in international financial centres (IFCs). Based on a dataset with extended jurisdiction coverage and sample length, foreign-owned IFC deposits declined globally by 24% or USD 410 billion during the period from 2008 to 2019. The commencement of automatic exchange of information is associated on average with a statistically significant 22% reduction in IFC bank deposits held by non-IFC counterparty jurisdictions. The results show that exchange of information on request was associated with a reduction of around 10% during the early years of implementation. Robustness checks show that voluntary disclosure programmes do not drive the results. These findings highlight the effectiveness of the expansion of automatic exchange of informationand provide further evidence of the success of a comprehensive multilateral approach towards international tax transparency
Keywords: Taxation